Effect of Self Efficacy, Subjective Norms, and Level of Education on Student Entrepreneurship Interest - Kusumaningtyas, Nadya Dwi; Chandra, Kusuma; Hartanto, Selamet (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the effect of self efficacy, subjective norms, and level of education on entrepreneurial interest. This research took a sample of students in cirebon. The sampling technique used in this study was sampling through purposeful sampling. The sample in this study amounted to 90 students who live in cirebon. In this study using multiple regression analysis techniques and data processed using the spss program. The results of this study are self efficacy has a positive effect on entrepreneurial interest has a negative effect on entrepreneurial interest.